2016
DOI: 10.1007/s10144-016-0552-3
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent reproduction causes winter crashes in a common vole population

Abstract: Common voles in western France exhibit three‐year population cycles with winter crashes after large outbreaks. During the winter of 2011–2012, we monitored survival, reproduction, recruitment and population growth rate of common voles at different densities (from low to outbreak densities) in natura to better understand density dependence of demographic parameters. Between October and April, the number of animals decreased irrespective of initial density. However, the decline was more pronounced when October d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…; Pinot et al . ) or maternal effects (Inchausti & Ginzburg ) can promote cycling. Using a combination of models and data, Kendall et al .…”
Section: Zooming In: the Influence Of Demography And Trait Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Pinot et al . ) or maternal effects (Inchausti & Ginzburg ) can promote cycling. Using a combination of models and data, Kendall et al .…”
Section: Zooming In: the Influence Of Demography And Trait Evolutionmentioning
confidence: 99%
“…Much of cycle theory considers changes in survival as the likely proximate driver of cycles of herbivores (Berryman 2002). However, changes in reproduction rates through direct influence of the environment (Łomnicki 1995;Smith et al 2006;de Roos et al 2009;Pinot et al 2016) or maternal effects (Inchausti & Ginzburg 2009) can promote cycling. Using a combination of models and data, Kendall et al (2005) showed that while parasitism and maternal effects (maternal body size affects the performance of offspring) can each qualitatively explain pine looper moth cycles, the latter provides parameter estimates that better match empirical measurements.…”
Section: Stage Structure Changes In Vital Rates and Interactions Betmentioning
confidence: 99%
“…The population dynamics of most grass-feeding vole species, in particular those of the genus Microtus, are driven by delayed density-dependent processes (e.g., Bjørnstad, Falck, & Stenseth, 1995). Demographically, this can be mediated by variation in the timing of onset of their spring reproduction, which is delayed by high population densities in the previous year (Ergon, Ergon, Begon, Telfer, & Lambin, 2011;Pinot et al, 2016). Theoretical studies have suggested that such density-dependent impacts on breeding season length alone have the potential to generate population cycles in seasonal environments (Smith, White, Lambin, Sherratt, & Begon, 2006), while in the field, voles transplanted at the start of winter between grassland areas differing in the phase of their cycle have been shown to take on the characteristics of vole populations in their new environment (Ergon, Lambin, & Stenseth, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Дефіцит ресурсів унеможливлює підтримання існування великих агрегацій. Напружене розмноження та швидкий темп збільшення популяції характерні для фази росту, а також літніх місяців (Lindén, 2010;Pinot et al, 2016). У такі періоди вже існуючі компактні агрегації починають швидко змінюватися, проте не за рахунок ущільнення, а через збільшення площі (експансії у просторі).…”
Section: обговоренняunclassified